GES characterization of newborns, evaluated with ABR at Hernán Henríquez Aravena Hospital, during 2007-2011 and applications for the GES Protocol - Henríquez Vallejos, Sandra; González Gavilán, Daniela; Pérez Sanhueza, Gonzalo (Revista Chilena de Salud Pública, 2013)
The number of newborns who are diagnosed in Hernán Henríquez Aravena Hospital of Temuco described in the exam of Auditory evoked potential, through empirical evidence. This is the last test that GES protocol indicates to confirm or discard hearing loss in newborns. By taking a representative sample of all the children tested from 2007 to 2011, also by analyzing data from 793 children, with the SPSS version 20.0 statistical package, which were referred to diagnostic confirmation for having referred twice in the auditory potential of screening (for infants) and all those newborns that in their medical controls with specialists such as pediatricians, ENT or general practitioners, hearing problems were detected. Being a quantitative, longitudinal, and descriptive study, so it was repeated to a sixth examination (evoked responsed audiometry and tympanometry) to all those children who had a C or B tympanometric curve for having acute middle otitis in one or both ears. By obtaining two populations of preterm (with risk factors) and no preterm (no risk factors) in both groups, degrees of sensorineural hearing loss that ranged from mild to severe in different percentages were found. It allowed characterizing the population of infants with hearing impairment with and without risk factors, revealing the importance of conducting a hearing test to all newborns in order to detect it immediately and enable those children who require it.